Financial reporting standards : a comparative synthesis - Maimona, Muhammad A.; Adejola, Adebayo Paul (Kaduna, Nigeria : Joyce Graphic, 2010)
The book is product of long time research in financial reporting standards that exposes the differences that exists in the preparation and presentation of financial information. It is expected to network the use of financial standards, guide and prepare users of financial reports.
Includes bibliographical references and index.
oif 23/10/14
Loan
Keywords: Accounting -- Standards; Financial statements -- Standards; Accounting